2004
DOI: 10.1002/cii.121
|View full text |Cite
|
Sign up to set email alerts
|

ESRT and MCL correlations in experienced paediatric cochlear implant users

Abstract: The use of electrically evoked stapedius reflex thresholds (eSRT) has been suggested as a useful means for creating a cochlear implant speech processor programme. Studies in adults have shown that there is a high correlation between eSRT programmes and programmes created through behavioural testing. This study assessed the viability of using eSRT to create speech processor programmes in children, an often difficult-to-test population. Seven children with an average cochlear implant experience of 1.1 years part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 8 publications
0
12
0
1
Order By: Relevance
“…The ESR method has also been used to program CI speech processors in pediatric populations Lorens et al 2004;Caner et al 2007;Walkowiak et al 2010;Van Den Abbeele et al 2012) and was reported to cause less discomfort than traditional techniques (Bresnihan et al 2001). The correlation between the ESRT and C-level in children (R = 0.82) is similar to the reported value for adults (Hodges et al 1997;Kosaner et al 2009).…”
Section: Introductionmentioning
confidence: 54%
“…The ESR method has also been used to program CI speech processors in pediatric populations Lorens et al 2004;Caner et al 2007;Walkowiak et al 2010;Van Den Abbeele et al 2012) and was reported to cause less discomfort than traditional techniques (Bresnihan et al 2001). The correlation between the ESRT and C-level in children (R = 0.82) is similar to the reported value for adults (Hodges et al 1997;Kosaner et al 2009).…”
Section: Introductionmentioning
confidence: 54%
“…ESRTs also decreased from the apical to the basal regions. It also has been reported that correlations of ESRT with behaviorally set MCL levels weaken in basal regions (25,26).…”
Section: Discussionmentioning
confidence: 93%
“…35 ESRT may be a more helpful tool for predicting a patient's C/M levels, and ESRT remains stable/consistent over time postoperatively for both children and adults. [36][37][38][39][40][41][42][43][44] ESRT is similar to AR thresholds, where the static admittance of the ear canal is monitored in response to varying amounts of sound input delivered through the CI. Despite its potential clinical utility, ESRT may not be successfully measured in approximately 20 to 30% of patients.…”
Section: Treatment and Follow-up Care For CI Usersmentioning
confidence: 99%